2(x+3)=7(x-3)-8

Simple and best practice solution for 2(x+3)=7(x-3)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)=7(x-3)-8 equation:



2(x+3)=7(x-3)-8
We move all terms to the left:
2(x+3)-(7(x-3)-8)=0
We multiply parentheses
2x-(7(x-3)-8)+6=0
We calculate terms in parentheses: -(7(x-3)-8), so:
7(x-3)-8
We multiply parentheses
7x-21-8
We add all the numbers together, and all the variables
7x-29
Back to the equation:
-(7x-29)
We get rid of parentheses
2x-7x+29+6=0
We add all the numbers together, and all the variables
-5x+35=0
We move all terms containing x to the left, all other terms to the right
-5x=-35
x=-35/-5
x=+7

See similar equations:

| 159=3(-8x-3) | | 3x-17+5x-3=180 | | 3+8-3z-5-9z-1-6-4=12z-5 | | -4(-v-5)-(5v-6)=18 | | 0.04(2c-76)=-0.8(c-5) | | 20(2-x)+3=2x-5x | | 9h+5=12.50h | | 11(2-x)+3=2x-5x | | 0(2-x)+3=2x-5x | | 30/y=70/100 | | 7(2-x)+3=2x-5 | | 6(2-x)+3=2x-5x | | 4+-1=-x+9 | | 3(e+4)=-12 | | 28,500+75y=42,000 | | 5y-18y=-2(2-6y) | | 8=5x/2x-3 | | 96+8m=10 | | 3x=11=x=21 | | -22=-2-4y | | 8-4x+3=2x-5x | | 2^10n=24 | | S=3a | | x³+12x²+48x+64=0 | | (w+4)^2=2w^2+13w+10 | | -5(x+-3)+9x=39 | | 3d-6=-14 | | d-(-28)=41 | | 9(v−83)=54 | | y=2100/2 | | y=21002 | | 29=f/5+21 |

Equations solver categories